Sindroma Nefrotik - Muhammad Arvin Harwansya; Rahmawati Rahmawati (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Nephrotic syndrome is a group of diseases characterized by massive proteinuria that causes hypoalbuminemia, resulting in hyperlipidemia, edema, and various complications. One of the etiologies of nephrotic syndrome itself is primary and secondary glomerulonephritis in the form of infection, malignancy, connective tissue disease, drugs or toxins and due to systemic diseases. The incidence of nephrotic syndrome cases in adults does not have a significant difference between genders, where the cases are 3 per 100,000 population. The broad clinical manifestations of nephrotic syndrome require health workers to conduct anamnesis, physical examination, and supporting examinations carefully. When nephrotic syndrome has been established, management will be carried out. Management that can be given to this disorder is non-pharmacological such as a low protein and salt diet and pharmacological especially for the underlying disease. Non-specific treatment to reduce proteinuria, control edema, and treat complications that may occur. The prognosis for nephrotic syndrome depends on the underlying cause.